Luminescence Characteristics of Dy3+/Eu3+ Doped CaBi2Ta2O9 Phosphors. (1st June 2022) - Yang, Yu-Guo; Luo, Qing-Li; Wei, Lei; Yu, Hua-Jian; Qiu, Cheng-Cheng; Li, Qing-Gang; Wang, Xu-Ping; Liu, Bing; Wang, Ji-Yang; Li, Jing-Feng
Abstract : The Dy 3+ /Eu 3+ doped CaBi2 Ta2 O9 phosphors had been obtained via the sintering processes at 1200 °C for 3 h. The phase and luminescence performance of the prepared phosphors had been researched. The X-ray diffraction results indicate the pure orthorhombic phase of the prepared phosphors. When the phosphors are excited at 355 nm, the Dy 3+ /Eu 3+ single doped CaBi2 Ta2 O9 phosphors exhibit the characteristic emission bands corresponding to Dy 3+ and Eu 3+, and the Dy 3+ /Eu 3+ codoped CaBi2 Ta2 O9 phosphors exhibit tunable luminescence on account of the Dy 3+ → Eu 3+ energy transfers. In this process, the dipole-dipole interaction is dominated.